The emergence of footballing cultures : Manchester, 1840-1919 - James, Gary, 1967- (Book collections on Project MUSE., 2019)
This study of Manchester football, by leading football historian Gary James, considers the sport's emergence, development and establishment through to its position as the city's leading team sport. The period from 1840 to 1919 saw football in Manchester develop from an inconsequential, occasionally outlawed activity, into a major business with a variety of popular football clubs and supporting industry. This book makes a distinct and original contribution to the historiography of sport. It is the first academic study into the development of association football in Manchester, and is directly linked to the current state of knowledge and debates within sports history on football's origins. It adds regional focus to inform the wider debate, contextualising the growth of the sport in the city and identifies communities who propagated and developed football. Robust research should ensure that this becomes the benchmark study of regional football.